Anatomically realistic ultrasound phantoms using gel wax with 3D printed moulds. (4th January 2018) - Maneas, Efthymios; Xia, Wenfeng; Nikitichev, Daniil I; Daher, Batol; Manimaran, Maniragav; Wong, Rui Yen J; Chang, Chia-Wei; Rahmani, Benyamin; Capelli, Claudio; Schievano, Silvia; Burriesci, Gaetano; Ourselin, Sebastien; et al.
Abstract: Here we describe methods for creating tissue-mimicking ultrasound phantoms based on patient anatomy using a soft material called gel wax. To recreate acoustically realistic tissue properties, two additives to gel wax were considered: paraffin wax to increase acoustic attenuation, and solid glass spheres to increase backscattering. The frequency dependence of ultrasound attenuation was well described with a power law over the measured range of 3–10 MHz. With the addition of paraffin wax in concentrations of 0 to 8 w/w%, attenuation varied from 0.72 to 2.91 dB cm −1 at 3 MHz and from 6.84 to 26.63 dB cm −1 at 10 MHz. With solid glass sphere concentrations in the range of 0.025–0.9 w/w%, acoustic backscattering consistent with a wide range of ultrasonic appearances was achieved. Native gel wax maintained its integrity during compressive deformations up to 60%; its Young's modulus was 17.4  ±  1.4 kPa. The gel wax with additives was shaped by melting and pouring it into 3D printed moulds. Three different phantoms were constructed: a nerve and vessel phantom for peripheral nerve blocks, a heart atrium phantom, and a placental phantom for minimally-invasive fetal interventions. In the first, nerves and vessels were represented as hyperechoic and hypoechoic tubular structures, respectively, in a homogeneous background. The second phantom comprised atria derived from an MRI scan of a patient with an intervening septum and adjoining vena cavae. The third comprised the chorionic surface of a placenta with superficial fetal vessels derived from an image of a post-partum human placenta. Gel wax is a material with widely tuneable ultrasound properties and mechanical characteristics that are well suited for creating patient-specific ultrasound phantoms in several clinical disciplines.